Memórias do antigo coco de roda: dos processos de resistência no município de Conde-PB às relações com a educação popular - Silva, Cícero Pedroza da (2023)
Coco de Roda is a meeting of people with themselves, making them discover themselves, because Coco has the power of meeting − with others, with education, with politics, with nature, with the idea of cosmos, with cultural matrices, with ancestry. Coco de Roda is an ancestral toy, it is a work song, an intangible heritage, just as the masters of Coco are intangible heritage. And, whoever dances the Coco is called a joker. The present study, MEMORIES OF THE OLD COCO DE RODA: from the processes of resistance in the municipality of Conde-PB to the relations with Popular Education, has as its object of investigation the Coco de Roda in the old meetings of Coco on the beach of Jacumã, hence the denominator of Ancient Coco de Roda, which has roots in quilombola territories. Our main objective is to understand the origin and historical, cultural, social and political contribution of the movement of the Antigo Coco de Roda in the municipality of Conde-PB, observing its processes of resistance and its epistemological relations with principles of Popular Education. The research problem was defined based on the following question: from the origin of the Ancient Coco de Roda in the municipality of Conde-PB, is it possible to explain the resistance processes arising from this cultural expression and its possible connections with popular education? With the methodology of Oral History and Memory, we bring to the debate Bosi (1994), with the importance of memory for society; Meihy (2013), with how to do and how to think about Oral History; with Oliveira (2005), through the perspective of the Revistas da Associação Brasileira de História Oral, and the theoretical framework in Freire (2015), rereading and rewriting the pedagogy of the oppressed as the overcoming of domesticating education by a problematizing/liberating one. Methodologically situated in the precepts of the qualitative research approach, we anchor ourselves in a theoretical-critical perspective from the oral history and the memory in a locus of investigation of many fights and social facts relevant to the history of the municipality of Conde-Paraíba, specifically in four territories: the former quilombos of Gurugi and Ipiranga, the Fishermen's Village of Jacumã and the Dona Antônia rural settlement. For its accomplishment, the subjects of the research are the players of the Antigo Coco de Roda in the municipality of Conde-PB. We conducted interviews for three months, with a semi-structured script, following the use of a recorder; form to identify the profile of the interviewees and document analysis, we made a photographic coverage and used as sources the songs of the coconuts, the photos and the old videos, which refer us to the origin of Coco de Roda in the municipality. Using oral history and memory, we developed a critical analysis based on systematic observation, in order to better interpret the reality of those involved in this research. In general, the results revealed that the Coco de Roda Popular Culture movement was always present in the struggles and achievements of agrarian reform in the surveyed territories, and that, from play to resistance, Coco de Roda remains alive in people's memory, Thus, the thesis defended here is that the Ancient Coco de Roda reflects not only historical processes of popular resistance, but also that there is, in it, an epistemological relationship with principles of Popular Education.